Animal armor - Marsh, Laura F.; National Geographic Society (U.S.) (Washington, D.C. : National Geographic Kids, 2018)
"Information about animals shells, scales, spikes and other outer coverings, for young children learning to read"--
A cover of armor -- Spikes and spines -- Strong shells -- Fun facts about animal armor -- Super scales -- Armor for you? -- What in the world?
OSLIS\Gale Nat Geo eBooks(2/2/23).
Ages 4-6.
Preschool, excluding K.
Print version record and CIP data provided by publisher; resource not viewed.
OverDrive (READ) format features optional read-along narration.
Keywords: Armored animals -- Juvenile literature; Animal defenses -- Juvenile literature; Adaptation (Biology) -- Juvenile literature; Electronic books- OSLIS